2012
DOI: 10.1007/978-94-007-5179-8_4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cadmium in Biological Samples

Abstract: Analyses of cadmium concentrations in biological material are performed using inductively coupled plasma mass spectrometry (ICP-MS) and atomic absorption spectrometry (AAS), but also electrochemical methods, neutron activation analysis (NAA), and X-ray fluorescence spectrometry (XRF). The predominant sample matrices include blood, plasma, serum, and urine, as well as hair, saliva, and tissue of kidney cortex, lung, and liver. While cadmium in blood reveals rather the recent exposure situation, cadmium in urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 57 publications
0
12
0
1
Order By: Relevance
“…Inductively coupled plasma mass spectrometry (ICP-MS) and, sometimes, atomic absorption spectrometry (AAS) are used for the determination of cadmium in biological samples. Other techniques that may be used are anodic stripping voltammetry, neutron activation analysis, and X-ray fluorescence spectrometry [18].…”
Section: Methods and Problems Of Chemical Analysismentioning
confidence: 99%
“…Inductively coupled plasma mass spectrometry (ICP-MS) and, sometimes, atomic absorption spectrometry (AAS) are used for the determination of cadmium in biological samples. Other techniques that may be used are anodic stripping voltammetry, neutron activation analysis, and X-ray fluorescence spectrometry [18].…”
Section: Methods and Problems Of Chemical Analysismentioning
confidence: 99%
“…1,2,3 This kind of information can be obtained through the analysis of blood, as blood is the medium for the transport of essential and toxic trace elements. 1 The elemental determination in blood samples has been carried out through techniques such as atomic absorption spectrometry, 4,5,6,7,8 total reflection X-ray fluorescence (TXRF), 5,9 or hydride generation atomic fluorescence spectrometry (HG-AFS) 10 . However, due to the increasing demand in the number of elements to be determined in blood, alternative analytical methods are needed.…”
mentioning
confidence: 99%
“…Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES), 5,11,12 and, particularly, Mass Spectrometry (ICP-MS) 5,13,14,15,16,17 offer multi-elemental measurement capability, low detection limits, 18 wide dynamic range and short analysis time. 16 However, these techniques suffer from spectral as well as non-spectral interferences that may degrade the accuracy of blood analysis.…”
mentioning
confidence: 99%
“…Also, our results were in accordance with another study who found higher serum Cd concentration among the workers exposed to Cd compared to controls [ 22 ]. Other investigators [ 19 , 23 ] found a linear correlation between Cd concentration in serum and urine. The data is consistent with our finding where a significant positive correlation was found between the Cd concentrations in the serum and urine for the exposed group.…”
Section: Discussionmentioning
confidence: 87%